Impact of Nursing Methodology Training Sessions on Completion of the Virginia Henderson Assessment Record - Maria Lopez; Jose-Maria Jimenez; Mercedes Fernández-Castro; Belen Martin-Gil; Sara Garcia; Maria-Jose Cao; Manuel Frutos-Martin; Maria-Jose Castro (MDPI AG, 2020)
The Virginia Henderson model, integrated in the computer application GACELA Care, helps to standardise the nursing assessment and establish precise and personalised nursing diagnoses. The aim was to determine the extent of completion of the initial patient assessment record after nurses following a training programme on nursing methodology. A quasi-experimental, retrospective, randomised, observational, single-group study was performed in two stages: pre-training and post-training. Voluntary training sessions were held for the nurses that work with GACELA Care. The completion of the initial patient assessment using the needs of Virginia Henderson and the Norton scale was evaluated before and after the training sessions. Completion of the needs of Virginia Henderson in the initial patient assessment increased from 94.2% to 100% (p = 0.014). Completion of "hygiene/skin" increased significantly from 83.3% to 95.8% (pre-training and post-training, respectively). The remaining needs did not show statistical significance. Recording of the Norton scale increased from 63.13% to 92.5% (p < 0.001). The training sessions on nursing methodology have improved the completion of records and inclusion of normal characteristics, defining characteristics and risk factors, and improving pressure ulcer risk assessment through the Norton scale.